Discussion of facilities management as an academic discipline. Issue 1 (28th January 2014) - Junghans, Antje; O.E. Olsson, Nils
Abstract : Purpose: – The purpose of this paper is to explore what an academic discipline is and to apply and discuss this definition using facilities management as an example. The paper addresses an academic world that is facing the challenge of developing research and education in response to emerging disciplines and dealing with changes in the higher education system. Institutions are also confronted with the aim of the European Commission to "enhance the performance and international attractiveness of Europe's higher education". Design/methodology/approach: – A structured framework with six criteria outlining an academic discipline was applied to describe the state of the art of facilities management on the basis of systematical literature research. A survey was conducted with 215 contributions from the European Facility Management Network (EuroFM) and additionally 41 Master theses and 25 scientific papers were studied to gain up-to-date insights. Findings: – This paper provides a methodical approach on how to analyse and describe emerging disciplines. In addition, an overview of the state of the art in facilities management is shown. Research limitations/implications: – The methodological approach for the analysis of academic disciplines was tested using the example of FM. Before transferring the same methodology to other disciplines, researchers are advised to test and further develop the methodology for other disciplines. Practical implications: – This paper includes implications for the development and discussion of emerging disciplines in the academic world. Originality/value: – This paper contributes to a better understanding of academic disciplines and how they emerge.